Haar Wavelet Method for the System of Integral Equations - Hassan A. Zedan; Eman Alaidarous (Abstract and Applied Analysis, 2014)
We employed the Haar wavelet method to find numerical solution of the system of Fredholm integral equations (SFIEs) and the system of Volterra integral equations (SVIEs). Five test problems, for which the exact solution is known, are considered. Comparison of the results is obtained by the Haar wavelet method with the exact solution.